Q50, an iron-chelating and zinc-complexing agent, improves cardiac function in rat models of ischemia/reperfusion-induced myocardial injury - Korkmaz-İçöz, Sevil; Barnucz, Enikő; Loganathan, Sivakkanan; Li, Shiliang; Radovits, Tamás; Hegedűs, Péter; Zubarevich, Alina; Hirschberg, Kristóf; Weymann, Alexander; Puskás, László G.; Ózsvári, Béla; Faragó, Nóra; et al. (Circulation journal, 2013)
Background: Reperfusion of ischemic myocardium may contribute to substantial cardiac tissue damage, but the addition of iron chelators, zinc or zinc complexes has been shown to prevent heart from reperfusion injury. We investigated the possible beneficial effects of an iron-chelating and zinc-complexing agent, Q50, in rat models of ischemia/reperfusion (I/R)-induced myocardial infarction and on global reversible myocardial I/R injury after heart transplantation. Methods and Results: Rats underwent 45-min myocardial ischemia by left anterior descending coronary artery ligation followed by 24h reperfusion. Vehicle or Q50 (10mg/kg, IV) were given 5min before reperfusion. In a heart transplantation model, donor rats received vehicle or Q50 (30mg/kg, IV) 1h before the onset of ischemia. In myocardial infarcted rats, increased left ventricular end-systolic and end-diastolic volumes were significantly decreased by Q50 post treatment as compared with the sham group. Moreover, in I/R rat hearts, the decreased dP/dtmax and load-independent contractility parameters were significantly increased after Q50. However, Q50 treatment did not reduce infarct size or have any effect on increased plasma cardiac troponin-T-levels. In the rat model of heart transplantation, 1h after reperfusion, decreased left ventricular systolic pressure, dP/dtmax, dP/dtmin and myocardial ATP content were significantly increased and myocardial protein expression of superoxide dismutase-1 was upregulated after Q50 treatment. Conclusions: In 2 experimental models of I/R, administration of Q50 improved myocardial function. Its mechanisms of action implicate in part the restoration of myocardial high-energy phosphates and upregulation of antioxidant enzymes.  (Circ J 2013; 77: 1817-1826)
Gesehen am 18.11.2021